PERAN KEPERCAYAAN DALAM PERILAKU PELANGGAN UNTUK MENINGKATKAN PENJUALAN SECARA ONLINE - JAYA, DICKY CANDRA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
Online shopping is the activity of purchasing goods and services through the medium of the internet. Interestingly shopping online will change the behavior of customers and business practices in the future significantly. An important factor in online shopping is my belief. Confidence in the internet is an important consideration in making a purchase online. Many consumers to buy over the internet is due mainly to the issue of trust through payments online. The trust, in the sense of social psychological, is the belief that the other person will react in predictable ways. In short, confidence is the belief that one can rely on the promises made by others Most significant obstacles in the long term to the success of the internet as a commercial media on the market is the lack of consumer confidence on the internet. Factors – factors that could boost consumer confidence towards online shopping among others have knowledge of consumer technology, has a web site with an interesting look, have a quality web site that well, so consumers do not have the perception of risk in the transaction of purchasing products online. As for the number of ways to improve consumer confidence: 1) Relationship Antarindividu, 2)Use Media, 3)Web design.